"A paradox of power and marginality" : New Zealand nurses' professional campaign during war, 1900-1920 : thesis presented in fulfilment of the requirements for the degree of Doctor of Philosophy in History at Massey University - Rodgers, Jan. A. (Janice Ann) (Massey University, 1994)
In this thesis the paradoxes faced by New Zealand nurses as they set out to prove their abilities as nurses to the soldiers in World War I are examined in the context of the wider issue of establishing a profession. The discussion reflects on why nurses wanted to go to war. how they achieved this goal, and analyses the difficulties they encountered in order to achieve professional standing in this setting. It presents a view which challenges the traditional image of New Zealand military nurses as passive players willingly carrying out the traditional work of nursing, clean to the point of sterility, always serene, attending calmly and efficiently to the sick and injured soldiers. It is argued that from 1883, moves to promote a new system of New Zealand nursing included a deliberate campaign by nurses to limit the place of the untrained in the nursing work force. By fostering the feminine ideal of women's 'nature', their domesticity and duty to care, and assuming special skills to nurse the sick, the stratum of society from which nurses were drawn was more narrowly defined and men were largely excluded. This self imposed image of womanly propriety and feminine skills assisted the emergence of the reformed system of nursing in the civilian sphere, but in military structures it inevitably limited the place of nurses. Nurses contributed substantially to the nursing of soldiers and readily gained public recognition for this work, yet they struggled to gain credibility for professional nursing within military structures. In war the Victorian notions of women's 'natural' capabilities to nurse reinforced the perception that military nursing was just an extension of womanly qualities and hence was suitable for amateurs. The Victorian notions of gender adopted by the profession whereby its members were required to be womanly, dedicated and morally respectable served to endorse nurses as eminently suitable women to nurse soldiers separated from their own womenfolk. It did not assist nurses as they battled to reinforce their professional status within military hierarchies. Relative to the early hopes and aspirations the gains were small. In the final analysis the traditional belief that nursing was women's work limited the professional contribution that nurses were able to make in war.</
Keywords: Nurses; New Zealand; History